Time for decisions : US policy in the Western Hemisphere (Inter-American Dialogue WashingtonUS, 2000)
Provides an assessment of recent developments in Latin America and the Caribbean. Discusses the key challenges for US policy in the region, and sets forth a series of concrete recommendations for action by the new administration.
Keywords: FOREIGN POLICY